Preliminary study of electromagnetic energy absorption in the head due to the exposure of radio frequency at 900MHz - Mohd Hafizuddin, Mat; Mohd. Fareq, Abd. Malek, Dr.; M. S., Zulkefli; Ronald, Suzanna Harun (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org